Analisis Deskripsi Potensi Pariwisata Kota Batam Dalam Rangka Menjaring Wisatawan Mancanegara - Supriono Supriono (Jurnal Pariwisata Terapan, 2017)
Currently, Indonesia is increasing the role of Tourism as a contributing State Foreign Exchange. Batam is the 3rd contributors Foreign Tourists in Indonesia after Bali and Jakarta. This study aims to analyze and describe the potential of Batam City Tourism in order to capture Foreign Tourist so that it can contribute as much as 3.47% of the total foreign exchange of Indonesia. Its function is to be able to apply other regions in Indonesia. The focus of the analysis is Attraction Destination, Destination Facility, Accessibility, Imagery, and Price. By using descriptive qualitative analysis and interview for data retrieval. The result of the research indicates that the Destination is less attractive for foreign tourists in Batam because they interested in Destination that offer complete facilities and easiness of the accessibility. In addition, the Batam’s image are safe, comfortable, and the prices are relatively cheaper because Rupiah value compare than other currencies.